Enhancing deprescribing: A qualitative understanding of the complexities of pharmacist‐led deprescribing in care homes. (6th November 2022) - Birt, Linda; Wright, David J.; Blacklock, Jeanette; Bond, Christine M.; Hughes, Carmel M.; Alldred, David P.; Holland, Richard; Scott, Sion
Abstract: The English National Overprescribing Review identified that older people often take eight or more medicines a day. The report recommended pharmacists in primary care should take responsibility for addressing polypharmacy. Overprescribing is a safety concern in care homes as approximately half of older care home residents are prescribed at least one medicine that is unnecessary or now harmful. This predisposes them to adverse outcomes including hospitalisation and mortality. Deprescribing is the planned activity of stopping or reducing a medicine that may no longer be appropriate. Deprescribing, when performed by a pharmacist, is a multidisciplinary activity requiring close communication with general practitioners (GPs) and care home staff. A recently completed trial that integrated pharmacists with prescribing rights into older peoples' care homes found significant variation in proactive deprescribing activity. The aim of the current study was to specifically explore beliefs and practices of deprescribing in care homes. A qualitative approach was adopted to examine individual, social and contextual factors that acted as enablers and barriers to pharmacist deprescribing in care homes. Semi‐structured interviews were conducted with participants of the previous study (16 pharmacists, 6 GPs and 7 care home staff from Northern Ireland, Scotland and England). Using thematic analysis, we identified two themes: (a) Structures and systems affecting deprescribing, that is the context in which deprescribing happened, including team involvement and routine practices in GP surgeries and care homes; (b) Balancing risks when deprescribing, that is the perception of individual risk and social barriers were mitigated by understanding the medical background of residents. This supported the clinical understanding that risks from overprescribing were greater than risks from deprescribing. While deprescribing can involve all health professionals in the primary care team, these results suggest the pharmacist is well placed to lead the process; by having both clinical competence and professional willingness to drive this activity forward.